2015
DOI: 10.1080/1028415x.2015.1110952
|View full text |Cite
|
Sign up to set email alerts
|

Fructo-oligosaccharide improved brain β-amyloid, β-secretase, cognitive function, and plasma antioxidant levels in D-galactose-treated Balb/cJ mice

Abstract: Dietary FO (2.5-5% w/w diet) could attenuate the development of Alzheimer's disease, which was likely to be associated with its systematic antioxidant effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…Provided this limitation and the inability to make a direct comparison between OS controlled for dose, the data suggest that OS are capable of affecting and improving behavior yet had less clear of an impact on MRI and gene expression measures. While several studies have examined the effect of single oligosaccharide supplementation on cognition and brain development (Schmidt et al, 2015;Vázquez et al, 2015Vázquez et al, , 2016Jia et al, 2016;Savignac et al, 2016;Yen et al, 2017), here we explored the individual and combined effects of BMOS and HMO. The concentrations and diversity of OS in human milk vary to a great extent (McGuire et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Provided this limitation and the inability to make a direct comparison between OS controlled for dose, the data suggest that OS are capable of affecting and improving behavior yet had less clear of an impact on MRI and gene expression measures. While several studies have examined the effect of single oligosaccharide supplementation on cognition and brain development (Schmidt et al, 2015;Vázquez et al, 2015Vázquez et al, , 2016Jia et al, 2016;Savignac et al, 2016;Yen et al, 2017), here we explored the individual and combined effects of BMOS and HMO. The concentrations and diversity of OS in human milk vary to a great extent (McGuire et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…These result indicated that polyphenols, flavonoids, and non-polar components reported as functional components in tomatoes showed low possibilities of being active components in the functionality of TEE. Therefore, we suggest that the enhancing effect of TEE on cognitive function via BDNF production might be derived from poly/oligo-saccharides because TEE (50% ethanolic extract of tomato) contained various hydrophilic saccharides [43,44]. …”
Section: Discussionmentioning
confidence: 99%
“…Enhanced brain Aβ and amyloid precursor protein (APP) aggregation is closely associated with the development of AD (2). Extracellular amyloid plaques identified in AD, including Aβ 1-40 and Aβ , are derived from the larger APP by β-secretase and γ-secretase (3). An inhibitor of γ-secretase, semagacestat, has been reported to cause neurotoxicity, thus its clinical application is limited; therefore, a safe and effective suppressor of β-secretase may be considered a promising treatment approach (4,5).…”
Section: Introductionmentioning
confidence: 99%